1999
DOI: 10.1177/089686089901900110
|View full text |Cite
|
Sign up to set email alerts
|

The Standard Peritoneal Permeability Analysis in the Rabbit: A Longitudinal Model for Peritoneal Dialysis

Abstract: Objective The development of an experimental peritoneal dialysis (PD) model in rabbits to investigate peritoneal transport characteristics during a longitudinal follow-up and to assess normal values of these peritoneal transport parameters. Design Peritoneal transport parameters were determined in conscious, unrestrained rabbits by standard peritoneal permeability analysis adjusted for rabbits (SPAR). In this test a 1-hour dwell with 3.86% glucose dialysate is used. Dextran 70 (1 g/L) was added to the dialysat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The results from this study demonstrate that differences in UF characteristics between solutions containing two experimental glucose polymers with low polydispersity can be revealed using a rabbit model of PD. Rabbit models have been used for decades to evaluate PD solutions and peritoneal transport (15)(16)(17)(18)(19), but no such evaluations of dialysis solutions containing glucose polymers as osmotic agents have been published, except for our previous work in abstract form (10). There are two advantages to using a rabbit model, compared with a rat model, to evaluate dialysis solutions containing glucose polymers as osmotic agents: • The kinetics of UF in rat models of PD using icodextrin as the osmotic agent have been reported to differ significantly from those in human PD (13,(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…The results from this study demonstrate that differences in UF characteristics between solutions containing two experimental glucose polymers with low polydispersity can be revealed using a rabbit model of PD. Rabbit models have been used for decades to evaluate PD solutions and peritoneal transport (15)(16)(17)(18)(19), but no such evaluations of dialysis solutions containing glucose polymers as osmotic agents have been published, except for our previous work in abstract form (10). There are two advantages to using a rabbit model, compared with a rat model, to evaluate dialysis solutions containing glucose polymers as osmotic agents: • The kinetics of UF in rat models of PD using icodextrin as the osmotic agent have been reported to differ significantly from those in human PD (13,(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…The use of immunofluorescence labeling of epithelial and myofibroblast markers to identify cells undergoing EMT has been criticized. This provides only a static picture of the cellular response to injury, and we have shown that this picture looks very different depending on the point of time in the injury response [33] , [45] . Furthermore, there are criticisms of immunofluorescence studies including the nonspecificity of antibodies used and image-processing artifacts.…”
Section: Animal Models and Emtmentioning
confidence: 94%
“…In a standard acute model of PD, fluid is infused by intraperitoneal injection or a temporary catheter into the peritoneal cavity in mice, rats, rabbit, and sheep [43] , [44] . This model has been important in understanding properties of solute transport across the peritoneal membrane, changes in the interstitial matrix, and changes in attachment and morphology of mesothelial cells during injury [ [45] , [46] , [47] ]. The chronic infusion model of PD uses a peritoneal catheter implanted into rodents which then receive a daily or twice daily infusion of dialysis fluid for a span of 4–20 weeks [48] .…”
Section: Animal Models To Study Peritoneal Membrane Injurymentioning
confidence: 99%
“…High serum amylase levels are not unique to rats, occurring also in other rodents, such as mice and guinea pigs (51). Mouse (52)(53)(54) and rabbit models (55)(56)(57) have also been used in PD research. Although rabbit models allow PD to be performed for long periods of time and mimic certain aspects of the human situation (The ratio of peritoneal surface area and exchange volume in rabbits and human is similar.…”
Section: In-depth Reviewmentioning
confidence: 99%